Genome-wide association study for colorectal cancer identifies risk polymorphisms in German familial cases and implicates MAPK signalling pathways in disease susceptibility - Lascorz Puértolas, Jesús; Försti, Asta; Chen, Bowang; Buch, Stephan; Steinke, Verena; Rahner, Nils; Holinski-Feder, Elke; Morak, Monika; Schackert, Hans K.; Görgens, Heike; Schulmann, Karsten; Goecke, Timm; et al. (Carcinogenesis, 2010)
Genetic susceptibility accounts for ∼35% of all colorectal cancer (CRC). Ten common low-risk variants contributing to CRC risk have been identified through genome-wide association studies (GWASs). In our GWAS, 610 664 genotyped single-nucleotide polymorphisms (SNPs) passed the quality control filtering in 371 German familial CRC patients and 1263 controls, and replication studies were conducted in four additional case-control sets (4915 cases and 5607 controls). Known risk loci at 8q24.21 and 11q23 were confirmed, and a previously unreported association, rs12701937, located between the genes GLI3 ( GLI family zinc finger 3) and INHBA (inhibin, beta A) [ P  = 1.1 × 10 −3 , odds ratio (OR) 1.14, 95% confidence interval (CI) 1.05-1.23, dominant model in the combined cohort], was identified. The association was stronger in familial cases compared with unselected cases ( P  = 2.0 × 10 −4 , OR 1.36, 95% CI 1.16-1.60, dominant model). Two other unreported SNPs, rs6038071, 40 kb upstream of CSNK2A1 (casein kinase 2, alpha 1 polypeptide) and an intronic marker in MYO3A (myosin IIIA), rs11014993, associated with CRC only in the familial CRC cases ( P  = 2.5 × 10 −3 , recessive model, and P  = 2.7 × 10 −4 , dominant model). Three software tools successfully pointed to the overrepresentation of genes related to the mitogen-activated protein kinase (MAPK) signalling pathways among the 1340 most strongly associated markers from the GWAS (allelic P value < 10 −3 ). The risk of CRC increased significantly with an increasing number of risk alleles in seven genes involved in MAPK signalling events (P trend  = 2.2 × 10 −16 , OR per allele  = 1.34, 95% CI 1.11-1.61).
Gesehen am 10.03.2023